지상파 다채널방송 서비스 방식 비교 연구 - 이창형(Chang-Hyung Lee); 박성규(Sung-Kyu Park) (한국콘텐츠학회 논문지, 12(6), 2012)
The Terrestrial DTV service compliant with ATSC has been advancing for years. In KBA(Korean Broadcasters Association), a multi-channel service was broadcasted on air during the period of the 2006 FIFA World Cup Germany with the various type of MMS(Multi Mode Service) using MPEG-2 encoding method. MMS Service can provides not only one HD channel but also serveral additional services within 6MHz bandwidth. Using digital video compression technology(MPEG-2), many various programs such as HDTV, SDTV, Audio and Data are able to be transmitted within the same bandwidth. From November 2009, KBS has been preparing an advanced MMS service, 'Korea-View' which has both methods of encoding, MPEG-2 and H.264 that is compliant ATSC mobile standard, A/153. Korea-View is a kind of multi-channel broadcast service to provide one HD and 3 SD programs with the bandwidth of 6MHz. Terrestrial multi-channel service is required to focuse on expanding viewer service. Such Terrestrial multi-channel services will contribute to transferring to digital broadcasting and to extending the viewers' welfare. Due to advances in digital technology, Pay-TV channels has increased to hundreds. Even though digital switchover is being proceeded, terrestrial broadcasters have been unable to deliver multi-channel services. In this paper, technical features and differences of MMS and Koreaview will be analyzed regarding terrestrial multi-channel broadcasting services, and the politic direction will be proposed in accordance with introduction of future service. 지상파 디지털방송의 표준인 ATSC 서비스가 진화하고 있다. 한국방송협회(KBA)는 2006년 독일 FIFA 월드컵방송 기간 동안 MPEG-2 압축방식을 사용한 지상파 다채널방송인 MMS(Multi Mode Service)를 시험 방송하였다. MMS는 하나의 HD채널을 제공하면서 6MHz 대역 내에서 다양한 부가서비스를 제공한다. 비디오 압축 기술(MPEG-2)을 사용하여 HDTV, SDTV, Audio 뿐만 아니라 Data신호를 전송할 수 있다. 지난 2009년 11월, KBS는 MMS서비스보다 진화한 코리아뷰(KoreaView)를 제안하였다. 코리아뷰의 압축방식은 MPEG-2와 H.264를 혼합한 방식으로 미국의 모바일방송 표준(A/153)과 동일한 방식이다. 코리아뷰는 다채널방송서비스로 6MHz대역 내에서 HD와 3개의 SD프로그램을 제공한다. 지상파 방송의 다채널 서비스는 시청자서비스 확대에 주목할 필요가 있다. 또한 지상파 방송의 다채널 서비스는 디지털 전환을 촉진시키고 시청자들의 선택권을 확대시킨다. 디지털기술의 발전으로 유료방송 채널은 수백 개로 증가하고 있다. 그러나 지상파 방송은 디지털 전환이 추진되고 있지만 다채널 서비스를 제공하지 못하고 있다. 본 연구는 지상파 다채널 서비스인 MMS와 코리아뷰의 기술적 특징과 차이를 분석하고, 향후 서비스 도입에 따른 정책적 방향을 제시하였다.